O ensino de botânica: uma proposta nos cursos de nível médio em meio ambiente do IFAM/CMC - Matos, Lana Barros de (2016)
The research entitled The Teaching of Botany: a proposal in the middle level courses in the Environment of the IFAM / CMC seeks to contribute in the teaching of Botany, area of the curricular component of the degree in Biological Sciences of the Federal Institute of Education, Science and Technology of Amazonas ( IFAM). In this sense, the teaching of this theme is an important and current thing for society, as one of the ways to understand the environment that surrounds us. The problems raised by this research have their birth in the general knowledge that the lack of resources and strategies in Botany teaching culminate in overly theoretical, tiring and unattractive classes. Today's school needs students who are trained to give their opinion in the world, understand the causes of phenomena on the planet and recognize that many times these causes are made by humans interacting in the environment. The references used in the research process sought to contribute to the understanding about the need to create strategies for teaching the theme. Therefore, the epistemological thinking necessary to the teaching of Sciences, the contribution of activities in non-formal spaces in the teaching of Botany, the didactic modalities in the teaching of Biology and in the practice of the teacher of the area were essential as well as to know the challenges that coexist between The teaching of the subject in question and the secondary education. As a methodological strategy, qualitative research traits were used, since among other factors it is a research that aims to integrate people in the search for solutions to a given problem, contextualizing in this way the practice where the beings of the research are inserted. In accordance with this approach, the curricular matrix of the course was analyzed, identifying in this document that the contents related to Botany did not have continuity in the second and third module, leaving the entire subject to be presented in the first module. This shows weakness of educational actions, since a great amount of information is condensed in a single period. As a data collection instrument, questionnaires were used in order to collect data referring to the contents of Botany treated in the medium level course in the Environment. The objective was to elaborate a didactic sequence for the teaching of Botany to be applied to the technical course on the Environment of IFAM as a way of contributing to the teaching and learning process of this area. The application of said sequence gave the students, greater interaction with the object of study in this case, the plants of the Institute. The actions that followed allowed the plating of species for identification purposes and the creation of a board and digital game under the title "Vegetable Species at IFAM: a walk through our house."